Reddit quarantined: Can changing platform affordances reduce hateful material online? - Simon Copland (Internet Policy Review, 2020)
This paper studies the efficacy of the Reddit's quarantine, increasingly implemented in the platform as a means of restricting and reducing misogynistic and other hateful material. Using the case studies of r/TheRedPill and r/Braincels, the paper argues the quarantine successfully cordoned off affected subreddits and associated hateful material from the rest of the platform. It did not, however, reduce the levels of hateful material within the affected spaces. Instead many users reacted by leaving Reddit for less regulated spaces, with Reddit making this hateful material someone else's problem. The paper argues therefore that the success of the quarantine as a policy response is mixed.
Keywords: 300; Reddit; Affordances; Misogyny; Manosphere; Digital platforms; Online platforms